2014
DOI: 10.5664/jcsm.3710
|View full text |Cite
|
Sign up to set email alerts
|

A Psychometric Study of the Fear of Sleep Inventory-Short Form (FoSI-SF)

Abstract: Although all items are recommended for clinical purposes, the data support the use of the 13-item FoSI-SF for research purposes. Replication of the factor structure in clinical samples is needed. Results are discussed in terms of limitations of this study and directions for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 30 publications
0
34
1
Order By: Relevance
“…In turn, poor daily sleep efficiency was associated with poor sleep quality. Relatedly, our findings indicate that baseline fear of sleep was associated with poor sleep quality, which is consistent with cross‐sectional research among trauma‐exposed individuals (Pruiksma et al ., ). In sum, this set of findings is consistent with the idea that PTSD‐specific factors (i.e.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In turn, poor daily sleep efficiency was associated with poor sleep quality. Relatedly, our findings indicate that baseline fear of sleep was associated with poor sleep quality, which is consistent with cross‐sectional research among trauma‐exposed individuals (Pruiksma et al ., ). In sum, this set of findings is consistent with the idea that PTSD‐specific factors (i.e.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, the FOSI measures avoidance and dread of nightmares or re‐experiencing, fear of loss of vigilance and night‐time vigilant behaviours. Prior research has suggested the FOSI possesses excellent internal consistency as well as temporal stability (Pruiksma et al ., ). In the current study, the FOSI also demonstrated excellent internal consistency ( α = 0.94).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…Whereas the BRAIN-K being a modification of an adult version may benefit from additional psychometric evaluations beyond the current age range. Also, the FoSI, measuring fear, being based on the adult version assessing fear in a rural trauma-exposed sample (150) warrants further psychometric scrutiny. In contrast to others, the RLS (117) proposes a difference in scores between two time points 14 days apart to identify RLS-related symptoms.…”
Section: Discussionmentioning
confidence: 99%